Analysis of Students Needs For Chemistry Module Based On Guided Discovery To Improve Critical Thinking Ability and Science Process Skills - Jekson Obianto Babys; Ashadi Ashadi; Sulistyo Saputro; Suryadi Budi Utomo (Syntax Corporation, 2023)
This research aims to find out students 'needs for chemistry modules based on guided discovery for thermochemical material to improve students' critical thinking skills and science process skills. Ninety students from three Senior High School in Surakarta participated in this research. The research method used is qualitative. Sources of data obtained from open questionnaires and interviews. The results of the analysis show that 90% of students state that there is a need for chemistry modules based on guided discovery for thermochemical material because the guided discovery stage can guide them to learn systematically so that what is learned is easier to understand, students stated that the chemistry module based guided discovery can help them think more critically and improve their science process skills. Learning activities with the guided discovery learning model will run well if supported by appropriate modules.